Pain Management in Aneurysmatic Subarachnoid Haemorrhage: A Survey of Nordic Physicians - Sariola, Hanna; Kalliomäki, Maija‐Liisa; Kiiski, Heikki; Raatikainen, Essi; Frösen, Juhana; Reinikainen, Matti; Savioja, Hanna; Møller, Kirsten; Lohela, Terhi; Takala, Riikka; Sigurdsson, Martin; Romundstad, Luis; et al. (Wiley, 2026)
Background
Headache caused by aneurysmatic subarachnoid hemorrhage (aSAH) is often severe and may persist long after the ictus. Pharmacological pain management can be challenging due to poor efficacy or adverse effects. Multimodal pharmacotherapy is often required. Lack of guidelines and good quality clinical studies on pain management has led to variation in pain management practices. Knowledge of current practice and goals of pain management in Nordic countries is lacking. We aimed to fill these knowledge gaps by conducting a survey targeting Nordic clinicians involved in aSAH treatment.
Methods
An electronic survey in English was sent to national coordinators in December 2023. The coordinators distributed the survey to intensivists, neurosurgeons, and other specialists treating aSAH patients in their respective countries. The survey contained 63 questions gathering background information, current aSAH pain management during the hospital stay and at hospital discharge, follow-up, and preferred outcome measures regarding a clinical trial on pain management in aSAH. The results were analysed and presented descriptively.
Results
We received 70 responses: 36 from Finland, 11 from Norway, 11 from Denmark, 5 from Sweden and 7 from Iceland. Respondents were intensivists (N = 46), neurosurgeons (N = 20), neurologists (N = 2), and others (N = 2). The most frequently used pain medications at ICUs were paracetamol, opioids, and non-steroidal anti-inflammatory drugs (NSAID). Most neurosurgeons (70%, N = 14) responded that they never prescribe opioids at hospital discharge for aSAH patients. The most preferred outcome for a clinical trial was patients' self-reported quality of life.
Conclusions
In the Nordic countries, paracetamol, opioids, and NSAIDs were reported as the most frequently used analgesics in the management of aSAH related pain in the ICU. Use of gabapentinoids was commonly reported by Danish respondents, unlike respondents from other Nordic countries. Neurosurgeons reported that they rarely prescribe opioids at hospital discharge.
Editorial Comment
This survey of Nordic clinicians involved in ICU and neurosurgical management of subarachnoid bleed (aneurysm) cases presents preferences for pain management in hospital and with discharge, as well as assessing clinician preferences for outcomes by which to assess pain management in these cases.